2020
DOI: 10.17220/ijpes.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Counselling on Anxiety Level from the Perspective of Ecological Systems Theory: A Quasi-experimental Pre-test - Post-test Control Group Study

Abstract: In this study, we aimed to examine how counseling service provided to college students, through a contextual clinical counseling model, affects the anxiety level of college students at a university in the east of Turkey. We followed a quasi-experimental with pretest-posttest and with control group design method. The experimental group comprised 205 and the control group comprised 75 college students. Seven supervisors with Ph.D. or MD degree in mental health professions provided weekly supervision to 120 couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Peer relationships play an increasingly important role in socialization during adolescence. Forming and maintaining positive peer relationships are important social tasks for all individuals, especially for adolescents (Tarhan et al, 2020). The same researchers found that poor peer relationships were associated with unsatisfactory developmental outcomes such as feelings of loneliness, social anxiety, distress, and low academic achievement.…”
Section: Peer Groupsmentioning
confidence: 99%
“…Peer relationships play an increasingly important role in socialization during adolescence. Forming and maintaining positive peer relationships are important social tasks for all individuals, especially for adolescents (Tarhan et al, 2020). The same researchers found that poor peer relationships were associated with unsatisfactory developmental outcomes such as feelings of loneliness, social anxiety, distress, and low academic achievement.…”
Section: Peer Groupsmentioning
confidence: 99%
“…The data in the previous section showed that using the Audio-Lingual Method effectively improved students' speaking skills. This is supported by the fact that the mean score of the post-test for the experimental group was higher than the mean score of the pre-test for the experimental group (TARHAN et al, 2020). The conclusion from the above explanation is that the primary goal of the Audio-Lingual Method is that learners can think critically when dealing with a problem in life, both personal problems and problem groups, to find a way out of the problems they face.…”
Section: Discussionmentioning
confidence: 84%
“…The result of the study proves that both type of therapy was effective in cognitive emotion regulation among the anxiety patients with P<0.001 and it was suggested for therapist to implement the schema and acceptance commitment therapy in psychological interventions and cognitive emotion regulations with anxiety patients. A research by Tarhan, Karaman and Nalbant (2020) on examining counseling service as a pre and post study design with university students in Turkey. The finding of this study proves that psychological counselling service provides a statistically significant decrease in anxiety symptoms for the students (clients).…”
Section: Literature Reviewmentioning
confidence: 99%